Resiliensi Keluarga Dengan Anak Gangguan Disintegratif Melalui Konseling Kelompok - Festa Yumpi Rahmanawati; Danan Satriyo Wibowo (Universitas Muhammadiyah Jember, 2017)
The purpose of this research was to explore how families with children with Childhood Disintegrative Disorder (CDD) who participated in group counseling that were able to move through the adverse situation that they face while raising a child with significant developmental needs and challenges. The theoretical framework that guided this research was family resilience. Qualitative research with case study approach was choosed to explore families with CDD. Observations and face-to-face interviews were conducted with each of the participants in their own home or in a school setting. The first question research focused on the experience of families who provided beneficial group counseling. Three themes emerged: a) focusing on child-positif behaviour target; b) accepting child in their ideal image realistically; c) providing motivation in positif parenting practice. The second question research focused on the experience of families who demonstrated willingness to find family resources after participated in group counseling. Four themes emerged: a) religious coping; b) positive seeking support; d) gratitude to attainable child competence.Key words: family resilience, disintegrative disorder, group couselling, case study